Effects of Mode of Preparation of Titanium Dioxide Nanotube Arrays on Their Photocatalytic Properties: Application to p-Nitroaniline Degradation - Nisreen Alshibeh Alwattar; Florence Vacandio; Laurent Vassalo; Thierry Djenizian; Bruno Coulomb; Jean-Luc Boudenne (Micro, 2023)
The aim of this study was to investigate the photoactivity of dioxide titanium (TiO2) nanotube films depending on different structure factors including pore size, tube length, tube wall thickness and crystallinity. Aqueous p-nitroaniline was used as a probe to assess the photocatalytic activity of titanium dioxide nanotube layers under UV irradiations. Self-organized titanium dioxide nanotube thin films were prepared by electrochemical anodization of titanium (Ti) foils and Ti thin films sputtered onto silicon (Si). The amorphous as-formed titanium nanotube layers were then annealed at different temperatures ranging from 450 to 900 °C in order to form crystalline phases. The structure and the morphology of the films were characterized by surface analysis techniques and scanning electron microscopy, respectively. The photocatalytic activity of the resulting TiO2 thin films was evaluated by monitoring the UV degradation of p-nitroaniline by UV spectrophotometry and by determining nitrification yields of by ion chromatography. The highest photocatalytic activity was exhibited for titanium nanotubes annealed at 450 °C. The presence of rutile -obtained for an annealing temperature of 900 °C—appeared to reduce the photodegradation yield of p-nitroaniline. Finally, the TiO2 nanotubes obtained from Ti foils revealed the most efficient photocatalytic properties.